2017
DOI: 10.3390/ph10020042
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycan Binding and Non-Endocytic Membrane Translocation of Cell-Permeable Octaarginine Monitored by Real-Time In-Cell NMR Spectroscopy

Abstract: Glycosaminoglycans (GAGs), which are covalently-linked membrane proteins at the cell surface have recently been suggested to involve in not only endocytic cellular uptake but also non-endocytic direct cell membrane translocation of arginine-rich cell-penetrating peptides (CPPs). However, in-situ comprehensive observation and the quantitative analysis of the direct membrane translocation processes are challenging, and the mechanism therefore remains still unresolved. In this work, real-time in-cell NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 75 publications
(101 reference statements)
2
18
0
Order By: Relevance
“…195 Takechi-Haraya et al employed real-time in-cell NMR spectroscopy and R 8 N-terminally modified with 19 F-4trifluoromethyl-L-phenylalanine ( 19 F-R 8 ) as a probe to monitor direct translocation into HL60 myeloid leukemia cells at 4 °C. 196 Rapid nonendocytic internalization was observed at 80−100 μM concentrations, which proceeded through initial association with cell-surface GAGs, followed by permeation through the membrane into the cytosol. Time-dependent measurements indicated that extracellular R 8 rapidly reached an equilibrium concentration in ∼5 min, with a transient increase in GAG-bound peptide that then rapidly diminished and gradual increases in membrane and cytosolic peptide until an equilibrium was reach in ∼10 min.…”
Section: Chemical Reviewssupporting
confidence: 55%
“…195 Takechi-Haraya et al employed real-time in-cell NMR spectroscopy and R 8 N-terminally modified with 19 F-4trifluoromethyl-L-phenylalanine ( 19 F-R 8 ) as a probe to monitor direct translocation into HL60 myeloid leukemia cells at 4 °C. 196 Rapid nonendocytic internalization was observed at 80−100 μM concentrations, which proceeded through initial association with cell-surface GAGs, followed by permeation through the membrane into the cytosol. Time-dependent measurements indicated that extracellular R 8 rapidly reached an equilibrium concentration in ∼5 min, with a transient increase in GAG-bound peptide that then rapidly diminished and gradual increases in membrane and cytosolic peptide until an equilibrium was reach in ∼10 min.…”
Section: Chemical Reviewssupporting
confidence: 55%
“…The energetic cost to transfer positively charged Arg from water to the interior of a membrane suggests that this process should be highly unfavourable, in striking contrast with the experimental evidence that CPPs cross the membrane quite easily on a timescale of minutes 68 . Our model reconciles a non-disruptive penetration mechanism with the apparently modest translocation energy barrier inferred from experiment, suggesting that once the peptide is deprotonated the hydrophobic barrier is much lower than previously thought.…”
Section: Resultsmentioning
confidence: 93%
“…GAGs interact with proteins in many biological systems, and as a consequence they have numerous biological and therapeutic functions [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In fact, GAGs can be considered the most exploited carbohydrates in the pharmaceutical market [ 14 ].…”
Section: Glycosaminoglycansmentioning
confidence: 99%
“…GAGs are also involved in the cell uptake of potentially useful drug-delivery systems. Takechi-Haraya and associates have in this issue described the contribution of GAGs in the non-endocytic direct cell membrane translocation of arginine-rich cell-penetrating peptides by studying the cell-permeation of octaarginine monitored through real-time in-cell 19 F NMR spectroscopy [ 21 ].…”
Section: Proteoglycansmentioning
confidence: 99%
See 1 more Smart Citation